ANALISIS MEKANIK DAN DIFRAKSI NANO KOMPOSIT TERMOPLASTIK HDPE - Eva Marlina Ginting; Erna Frida; Martha Marchofinece Padang; Nurdin Bukit (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The objective of this study was the manufacture of composite nano from ash particles of rice husk ash (RHA) which serves as a high density polyethylene (HDPE) thermoplastic filler. The composite nano-making process is carried out in an internal mixer of laboplastomill at a temperature of 150 Ã‚Â° C at a rate of 60 RPM for 10 min, blend HDPE with nano ASP in compositions (0.2,4,6,8 and 10) % of weight with a compatible 2% by weight and without a Polyethylene-grafted Maleic Anhydride (peg. MA). From the composite nanoscale results were analyzed the mechanical properties (tensile strength, elongation break and elastic modulus) and the diffraction pattern. The resultÃ‚  elongation and elasticity modulus analysis increase with increasing RHA nano composition a decrease of tensile strength and yield Strength of XRD analysis result of intercalation between HDPE thermoplastics and RHA nanoparticles.Keywords: RHA, HDPE,Ã‚  XRD, Mechanical properties.